A pre-Hispanic canoe or Wampo burial in Northwestern Patagonia, Argentina. - Alberto E Pérez; Rodrigo Moulian Tesmer; Juan Francisco Reyes Sánchez; José L Lanata; Andrea Medina; Miguel Chapanoff Cerda (PLoS ONE, 2022)
The burial of Individual 3 at the Newen Antug site, a young adult woman, with a pottery grave offering characteristic of the Late Pottery period and dated to 880 years BP, is an indirect burial in a wooden structure. The form and design comprise a wooden wampo or small canoe, or a symbolic representation of one, a metaphor in current and historical Mapuche society for the voyage to the final abode of the dead, located beyond a water body which must be crossed in a boat. This is the first find of a burial in a canoe structure in Argentinian Patagonia, and the most southern example on the whole continent. It is also the earliest record in Argentina of pottery of the Red on White Bichrome tradition used as a grave offering, extending the repertoire of characteristics shared between the two slopes of the Andes mountains during the pottery periods, including ritual as well as material aspects.